Pathways of Membrane Solubilization A Structural Study of Model Lipid Vesicles Exposed to Classical Detergents - Bjørnestad, Victoria Ariel (Langmuir : the ACS journal of surfaces and colloids, 2023)
Understanding the pathways of solubilization of lipid membranes is of high importance for their use in biotechnology and industrial applications. Although lipid vesicle solubilization by classical detergents has been widely investigated, there are few systematic structural and kinetic studies where different detergents are compared under varying conditions. This study used small-angle X-ray scattering to determine the structures of lipid/detergent aggregates at different ratios and temperatures and studied the solubilization in time using the stopped-flow technique. Membranes composed of either of two zwitterionic lipids, DMPC or DPPC, and their interactions with three different detergents, sodium dodecyl sulfate (SDS), n-dodecyl-beta-maltoside (DDM), and Triton X-100 (TX-100), were tested. The detergent TX-100 can cause the formation of collapsed vesicles with a rippled bilayer structure that is highly resistant to TX-100 insertion at low temperatures, while at higher temperatures, it partitions and leads to the restructuring of vesicles. DDM also causes this restructuring into multilamellar structures at subsolubilizing concentrations. In contrast, partitioning of SDS does not alter the vesicle structure below the saturation limit. Solubilization is more efficient in the gel phase for TX-100 but only if the cohesive energy of the bilayer does not prevent sufficient partitioning of the detergent. DDM and SDS show less temperature dependence compared to TX-100. Kinetic measurements reveal that solubilization of DPPC largely occurs through a slow extraction of lipids, whereas DMPC solubilization is dominated by fast and burst-like solubilization of the vesicles. The final structures obtained seem to preferentially be discoidal micelles where the detergent can distribute in excess along the rim of the disc, although we do observe the formation of worm- and rodlike micelles in the case of solubilization of DDM. Our results are in line with the suggested theory that bilayer rigidity is the main factor influencing which aggregate is formed